Using the Community-Based Participatory Research (CBPR) Approach in Childhood Obesity Prevention - Kumar, Janavi; Kidd, Tandalayo; Li, Yijing; Lindshield, Erika; Muturi, Nancy; Adhikari, Koushik (International Journal of Child Health and Nutrition, 2014)
Childhood and adolescent obesity has increased drastically in the past 30 years. While this is troubling, there is also evidence of large disparities among certain ethnic groups such as African American and Hispanic children and adolescents. The Community-Based Participatory Research (CBPR) Model emphasizes a collaborative, co-learning, mutually beneficial, and community-partnered approach to research. Unique aspects of this model include viewing community members as equal partners in non-hierarchical teams, working together in a strengths-based, action oriented research process. This review consists of an investigation of the CBPR approach, its important tenets, and why such an approach may be more effective for childhood and adolescent obesity intervention program development, especially in stratified communities.